Reoperation for complications within 90 days of minimally invasive glaucoma surgery. Issue 7 (July 2021) - Shalaby, Wesam Shamseldin; Bechay, Joseph; Myers, Jonathan S.; Lee, Daniel; Razeghinejad, Reza; Kolomeyer, Natasha Nayak; Katz, L. Jay; Shukla, Aakriti Garg
Abstract : The need for reoperations within 90 days after minimally invasive glaucoma surgery is low. Elevated intraocular pressure and gel microstent complications are the most common indications for reoperation. Abstract : Objective: To describe reoperations that occurred within 90 days of minimally invasive glaucoma surgery (MIGS) at a single institution over a 30-month period. Setting: Tertiary care hospital. Design: Retrospective case series. Methods: Charts of adult patients who underwent trabecular microbypass stents, gel microstents, and goniotomy procedures (including gonioscopy-assisted transluminal trabeculotomy) from October 1, 2017, to March 15, 2020, at Wills Eye Hospital were examined. Outcome measures were unanticipated reoperations within the first 90 days after MIGS procedures and the complications that led to these reoperations. Results: A total of 448 MIGS procedures were performed on 436 eyes of 348 patients over a 30-month period by 6 glaucoma surgeons. Of these, 206 (46.0%) were trabecular microbypass stents (198 iStent/iStent inject and 8 Hydrus), 152 (33.9%) were gel microstents, and 90 (20.1%) were goniotomy procedures. Combined phacoemulsification took place in 256 eyes (58.7%). Reoperation within 90 days took place in 23 (5.3%) of 436 eyes, including 16 (10.5%) of 152 eyes in the gel microstent group, 4 (2.0%) of 198 eyes in iStent/iStent inject group, and 3 (3.3%) of 90 eyes in the goniotomy group. Indications for reoperation were elevated intraocular pressure (IOP) in 16 (69.6%) of 23 eyes, gel microstent tip exposure with wound leakage in 3 (13.0%) of 23 eyes, and early gel microstent encapsulation without elevated IOP in 1 (4.3%) of 23 eyes. Two (8.7%) of 23 eyes required reoperation for intraocular lens complications, whereas 1 (4.3%) of 23 eyes had elevated IOP and aphakia requiring reoperation. Conclusions: The rate of reoperation within the first 90 days after MIGS was low. Elevated IOP and complications associated with gel microstents were the main indications for reoperation.